ER Stress and Iron Homeostasis: A New Frontier for the UPR - Susana J. Oliveira; Maria de Sousa; Jorge P. Pinto (Biochemistry Research International)
The C282Y mutation of HFE accounts for the majority of cases of the iron overload disease Hereditary Hemochromatosis (HH). The conformational changes introduced by this mutation impair the HFE association with β2-microglobulin (β2m) and the cell surface expression of the protein: with two major consequences. From a functional perspective, the ability of HFE to bind to transferrin receptors 1 and 2 is lost in the C282Y mutant, thus affecting hepcidin regulation. Also due to the faulty assembly with β2m, HFE-C282Y molecules remain in the endoplasmic reticulum (ER) as aggregates that undergo proteasomal degradation and activate an Unfolded Protein Response (UPR). UPR activation, regardless of the ER stress stimuli, was shown to reshape the expression profile of iron-related genes and to decrease MHC-I cell surface expression. The possibility of a HFE-C282Y-mediated interplay between the UPR and iron homeostasis influencing disease progression and the clinical heterogeneity among C282Y carriers is discussed. The responsiveness of the ER chaperone calreticulin to both ER and iron-induced oxidative stresses, and its correlation with HH patients’ phenotype, reinforce the interest of dissecting the UPR signaling/iron metabolism crosstalk and points to the potential clinical value of use of pharmacological chaperones in HFE-HH.